Miskonsepsi Gerak Melingkar Siswa - Asmirawati H. Daud; Supriatman; Amiruddin Hatibe (Jurnal Kreatif Online, 2021)
This study aimed to determine the percentage and description of students' misconceptions about circular motion. The subjects of this study consisted of 19 class XII students of SMA Negeri 5 Palu, then 5 respondents were selected for interviews. The instrument used was a reasoned multiple-choice test accompanied by a column of confidence level in answering questions (Three-Tier Diagnostic Test) totaling 17 questions. The data obtained were analyzed through a descriptive-qualitative approach by referring to the reasons and level of confidence as well as student interviews in answering questions about the concept of circular motion. The results showed that the level of students' misconceptions using the Three Tier Diagnostic Test was still relatively low with an average percentage of 34.05% when compared to the average number of students who did not understand the concept with an average percentage of 47.67%. In general, the misconceptions experienced by students in the circular motion material are varied for each concept tested.